2020
DOI: 10.3389/fpls.2020.00953
|View full text |Cite
|
Sign up to set email alerts
|

An Enzymatically Hydrolyzed Animal Protein-Based Biostimulant (Pepton) Increases Salicylic Acid and Promotes Growth of Tomato Roots Under Temperature and Nutrient Stress

Abstract: Biostimulants may be particularly interesting for application in agricultural and horticultural crops since they can exert a growth-promoting effect on roots. This may be important for promoting longitudinal and lateral root growth and therefore increasing belowground vegetative growth, which may in turn lead to improved aboveground vegetative growth and increased yields. Here, we examined the effects and mechanism of action of an enzymatically hydrolyzed animal protein-based biostimulant (Pepton) on the root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“… Ertani et al (2013) found that application of low doses (0.01 and 0.1 mL L –1 ) of an animal-derived PH, rich in amino acids, promoted maize seedling growth. In their experiments, other authors have applied the recommended dose: Casadesús et al (2020) applied an animal PH biostimulant (Pepton) at a recommended dose of 4 kg ha –1 to tomato plants; Cristiano et al (2018) treated snapdragon plants at a recommended dose of 0.1 g L –1 . The effectiveness of the application method (foliar spray or soil drench) appears to be species-dependent: Sestili et al (2018) showed that drench applications of PH were more effective in improving plant growth and total N uptake than foliar sprays in tomato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Ertani et al (2013) found that application of low doses (0.01 and 0.1 mL L –1 ) of an animal-derived PH, rich in amino acids, promoted maize seedling growth. In their experiments, other authors have applied the recommended dose: Casadesús et al (2020) applied an animal PH biostimulant (Pepton) at a recommended dose of 4 kg ha –1 to tomato plants; Cristiano et al (2018) treated snapdragon plants at a recommended dose of 0.1 g L –1 . The effectiveness of the application method (foliar spray or soil drench) appears to be species-dependent: Sestili et al (2018) showed that drench applications of PH were more effective in improving plant growth and total N uptake than foliar sprays in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…In maize treated hydroponically with 0.01 and 0.1 mL L –1 of a meat-hydrolysate biostimulant, Ertani et al (2013) found that root dry weight increased by +30 and +24%, respectively, compared to untreated controls. Casadesús et al (2020) assessed the effect of Pepton (an animal-based PH biostimulant) on tomato plants cultivated under suboptimal conditions. They found that Pepton had a positive effect on primary and lateral root growth through a direct influence of amino acid availability and through salicylic acid accumulation in response to stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…affecting the diverse physiological processes responsible for the stimulation of plant growth, the increment of nutrient use efficiency, resistance to abiotic stress and to biotic stresses, and the reduction in the use of chemical fertilisers. The application of these types of products does not cause an unfavourable impact on crop yield or quality [24,137,138]. In general, the hypothesised mechanisms of their action could be related to the modulation of gene expression, stimulation of amino acid biosynthesis, as well as enhancing antioxidant, osmolyte, protein, or pigment content [137].…”
Section: The Explanation Of the Differential Impact Of The Botanical Extractsmentioning
confidence: 99%
“…The application of these types of products does not cause an unfavourable impact on crop yield or quality [24,137,138]. In general, the hypothesised mechanisms of their action could be related to the modulation of gene expression, stimulation of amino acid biosynthesis, as well as enhancing antioxidant, osmolyte, protein, or pigment content [137]. To identify their mode of action, data concerning the detailed morphological, physiological, biochemical, and molecular analyses are required.…”
Section: The Explanation Of the Differential Impact Of The Botanical Extractsmentioning
confidence: 99%
“…They suggested that PH-treated plants were able to better cope with oxidative stress thanks to major changes in phytohormones and lipid profiles ( Paul et al, 2019a ). Lastly, Casadesús et al (2019 , 2020) assessed the beneficial effects of a product derived from enzymatic hydrolysis of animal proteins in tomato plants grown under water, temperature or nutrient stress suggesting that the positive effects on root growth are due to the increased biosynthesis of specific phytohormones ( Casadesús et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%